A revision of the west-palearctic Selenophorina (Coleoptera Carabidae Harpalinae) (XXXVI contribution to the knowledge of Coleoptera Carabidae) (Bollettino di zoologia agraria e bachicoltura, 2024)
In this work the western palaearctic Selenophorina are studied from the systematic and biogeographic point of view. After a synthetic history of this subtribe the combination of characters that can distinguish it from the other subtribes of Harpalini is given. Then a key for the determination of the three palaearctic genera Trichotichnus, Parophonus and Eriophonus and of the species belonging to each of these genera is reported. Bach species is then separately analysed from the nomenclatorial, systematic and distributional point of view. The taxon Eriophonus is raised to genus rank and transferred from the subtribe Harpalina to Selenophorina, furthermore the new synonimy Idiomelas Tschitscherine, 1900 = Trichotichnus Morawitz, 1863 is here proposed.
Keywords: revision; western palaearctic region; Coleoptera Carabidae Harpalini; Trichotichnus; Parophonus; Eriophonus